Improving smallholder farmers’ access to and utilization of climate information services in sub-Saharan Africa through social networks: a systematic review - Appiah, Collins E.; Quarmine, William; Osei-Amponsah, Charity; Okem, Andrew E.; Sarpong, D. B. (Elsevier, 2025)
The timely availability, access to, and utilisation of actionable climate information services (CIS) serve as an effective mechanism to address the impacts of climate change on smallholder farmers in Sub-Saharan Africa. Scholarly work from diverse contexts reveals that farmers’ social networks can be leveraged to promote access to CIS to mitigate climate risk. However, there is no synthesised information on the different insights that comprehensively demonstrate how social networks improve access to and utilisation of CIS among smallholder farmers in Sub-Saharan Africa. This paper employed a systematic literature review methodology to fill this knowledge gap. A stringent inclusion criterion was used to select 32 relevant peer-reviewed papers from an initial pool of 648 for analysis. Our study found farmers’ social networks to effectively promote CIS access and utilisation among smallholders in Sub-Saharan Africa. This was mainly as a result of the use of relatable local languages and the opportunity it provided for direct interaction during information flow. Smallholder farmers in big networks with stronger linkages, higher levels of participation, and a greater degree of trust, were identified to be more likely to utilise CIS to improve their livelihoods. Such farmers tend to have higher technical efficiency, productivity, and incomes. To harness social networks to scale up CIS access and utilisation, innovative platforms that can enhance social networking among farmers must be promoted and strengthened by agricultural devel opment stakeholders.